Analisis Pengaruh Tingkat Pengangguran Terbuka dan Pertumbuhan Ekonomi Terhadap Kemiskinan Tahun 2018-2022 - Utari, Yurdilla; Sumanto, Agus (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
TThis research aims to analyze the influence of the Open Unemployment Rate on poverty and Economic Growth on poverty in East Java Province in the 2018-2022 period using Time Series data obtained from the East Java Central Statistics Agency. The method used is Cross Section. The results obtained in this research are that Unemployment Rate has a positive effect on poverty and GRDP does not affect poverty in East Java in 2018-2022. In order to deal with this problem, it is necessary to improve infrastructure such as education, health, expanding employment opportunities, etc.